A method and system for integrated alignment of a titanium dioxide meta-lens and a fiber core

CN122984126APending Publication Date: 2026-10-27HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610640115.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,随着光学系统向高集成度、高分辨率的方向发展,传统方法逐渐显现出局限性:球面研磨透镜受加工工艺限制,微型化程度存在上限,且易产生球差、色差,聚焦精度难以满足应用需求;熔融拉锥光纤结构机械强度低,易断裂损坏,聚焦性能差;外接折射透镜体积大,无法实现全光纤一体化集成,装配对准难度大,系统集成度低

Benefits of technology

本发明所提供的二氧化钛超构透镜和光纤纤芯的集成对准方法,先在衬底上形成具有特定菲涅尔波带环图案的铜牺牲层,随后在牺牲层表面形成二氧化钛超构透镜,最后将超构透镜远离衬底的一侧与光纤端面通过紫外固化胶贴合。通过以特定图案的牺牲层作为后续的对准基础,本发明可以实现二氧化钛超构透镜图案与光纤端面的精确定位,提高对准精度,配合特定的超构透镜结构,本发明可以实现光纤端面超构表面聚焦效率的提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122984126A_ABST
    Figure CN122984126A_ABST
Patent Text Reader

Abstract

The application discloses a kind of integrated alignment method and system of titanium dioxide super-structure lens and optical fiber core, and it is related to micro-nano photonics technical field.The integrated alignment method of titanium dioxide super-structure lens and optical fiber core provided by the present application first forms the copper sacrificial layer with specific Fresnel band ring pattern on the substrate, then forms titanium dioxide super-structure lens on the surface of the sacrificial layer, and finally the side of the super-structure lens away from the substrate is bonded with the end face of the optical fiber by ultraviolet curing glue.By using the sacrificial layer with a specific pattern as the basis for subsequent alignment, the application can achieve precise positioning of the titanium dioxide super-structure lens pattern and the optical fiber end face, improving the alignment accuracy.Coupled with a specific super-structure lens structure, the application can improve the super-structure surface focusing efficiency of the optical fiber end face.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of micro-nano photonics technology, specifically to an integrated alignment method and system for a titanium dioxide metalens and an optical fiber core. Background Technology

[0002] Fiber optic focusing technology is a core technology for achieving miniaturization and integration of optical systems. Leveraging the advantages of low transmission loss, flexibility, and long transmission distance of optical fibers, it possesses irreplaceable application value in fields such as biomedical in vivo imaging, precision laser micromachining, and high-speed fiber optic communication. Traditional methods for achieving fiber optic focusing mainly include directly grinding and polishing the fiber end face to form a spherical microlens, fabricating a tapered focusing structure from fused ablation of the fiber, and attaching an external glass refractive microlens to the fiber end face. However, as optical systems develop towards higher integration and higher resolution, traditional methods are gradually showing limitations: spherically ground lenses are limited by processing technology, have an upper limit to miniaturization, and are prone to spherical aberration and chromatic aberration, making it difficult to meet application requirements in terms of focusing accuracy; fused ablation tapered fiber structures have low mechanical strength, are prone to breakage and damage, and have poor focusing performance; external refractive lenses are large in size, making it impossible to achieve full fiber-to-fiber integration, resulting in difficult assembly and alignment, and low system integration.

[0003] In recent years, the development of metasurfaces has provided a novel solution for fiber optic focusing. Metalenses, based on subwavelength artificial structural units, allow for precise control of parameters such as the phase and amplitude of incident light, thus enabling the construction of the phase distribution required for focusing. Compared to traditional focusing lenses, metalenses are two-dimensional, solving the problem of further miniaturization and micro-miniaturization of traditional curved lenses. Therefore, there are currently some cases of transferring metalenses to fiber end faces, but most are metallic metasurfaces. These metallic metasurfaces have high ohmic losses for electromagnetic waves in the visible light band, resulting in relatively low efficiency as focusing lenses. In contrast to metallic metasurfaces are dielectric metasurfaces. The dielectric materials used in dielectric metasurfaces, such as titanium dioxide, possess high refractive index (approximately 2.4-2.6), low optical absorption loss, and excellent chemical and mechanical stability in the visible to near-infrared band, effectively reducing device optical losses and improving focusing efficiency. Currently, there are related studies on integrating dielectric metalenses with fiber end faces. However, when directly applied to fiber focusing scenarios, existing integration schemes still have some insurmountable drawbacks, as follows: 1. The integration and alignment process of the dielectric meta-lens with the fiber end face is complex, resulting in low lens focusing efficiency.

[0004] 2. Alignment challenges of the metalens and fiber core: The alignment accuracy of the metalens and fiber core directly affects the mode matching of the fiber output mode field and the lens phase. Mismatch in position will cause a significant reduction in focusing efficiency.

[0005] Therefore, there is an urgent need for an integrated alignment method that can improve the focusing efficiency of the integrated structure of the dielectric metasurface and the fiber end face. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides an integrated alignment method and system for titanium dioxide metalenses and optical fiber cores.

[0007] The above-mentioned objective of this invention is achieved through the following technical solution: An integrated alignment method for a titanium dioxide metalens and an optical fiber core includes the following steps: S1. A photoresist layer is coated on the substrate surface. Exposure and development are performed according to the pattern of the copper sacrificial layer. After forming grooves in the copper sacrificial layer pattern on the photoresist layer surface, the copper sacrificial layer is deposited, and then excess photoresist is removed. The pattern of the copper sacrificial layer is a Fresnel zone ring, which includes multiple concentric rings. The inner and outer radii of the concentric rings satisfy... ,in Let n be the radius of the concentric annulus, where n is a positive integer; when n is odd, ... This represents the outer diameter value; when n is an even number, This refers to the inner diameter value; S2. A PMMA adhesive with a thickness of 700-1000 nm is coated on the surface of the copper sacrificial layer obtained in step S1. The PMMA adhesive is then exposed and developed according to the pattern of the titanium dioxide metalens. The titanium dioxide metalens comprises several nanocylinders, wherein the distance between the centers of any two adjacent nanocylinders is 280-350 nm. After development, a grooved PMMA adhesive is obtained. Titanium dioxide is deposited in the grooves to obtain the titanium dioxide metalens. The solid content of the PMMA adhesive is 7-10 wt%. S3. Remove the titanium dioxide from the surface of the PMMA adhesive, then pass it through a wavelength of [wavelength value missing]. The collimated light aligns the center of the titanium dioxide metalens obtained in step S2 with the center of the fiber core end face. The fiber core end face and the titanium dioxide metalens are then bonded together using UV-curable adhesive to form an integrated structure. S4. Immerse the integrated structure obtained in step S3 in FeCl3 solution to remove the substrate and copper sacrificial layer, and a titanium dioxide metalens can be prepared on the end face of the optical fiber core.

[0008] The integrated alignment method provided in this application designs the copper sacrificial layer into a structure that can utilize diffraction effects for transmission imaging. Based on this, this application can achieve precise positioning when integrating metalenses and optical fibers using collimated light, improving the alignment accuracy between the metalens and the fiber core and avoiding positional deviations. Furthermore, the minute positional deviation between the metalens array structure and the fiber core can fully utilize the focusing function of the metalens, thus this application can significantly improve the focusing efficiency of surface-mount metalenses on optical fibers.

[0009] It should be noted that the pattern of the copper sacrificial layer selected in step S1 of this application needs to be a Fresnel zone ring (including a central circle and multiple concentric rings concentric with the central circle) whose inner and outer radii satisfy a certain formula relationship with the collimated light wavelength. This ensures accurate positioning, and the structure also ensures that the copper sacrificial layer can be easily removed subsequently. Therefore, this structure can significantly improve the focusing efficiency of the integrated structure of this application. (Formula) In this context, the outer diameter value obtained when n is 1 is the radius value of the central circle of the Fresnel wave zone ring.

[0010] It should be noted that in step S2 of this application, a PMMA resist with a specific solid content is required to form a photoresist layer with a thickness of 700-1000 nm, corresponding to the required height of the nanopillars for the metalens, while the distance between the nanopillars is required to be in the range of 300-350 nm. Through experimental research, the inventors of this application have discovered that, under the premise of selecting a specific photoresist, a metalens with a specific structure can reduce the influence of higher-order diffraction. Furthermore, a specific thickness can improve the focusing efficiency of the lens. Therefore, this application can fully realize the maximum improvement in the focusing efficiency of the metalens.

[0011] It should be noted that the copper sacrificial layer used in this application should be removed during subsequent use to avoid affecting focusing. The inventors of this application discovered that immersion in FeCl3 solution can remove the ITO substrate and the copper sacrificial layer.

[0012] In specific embodiments of this application, the solid content of the PMMA adhesive refers to the mass fraction of the solute PMMA polymer in the solvent anisole.

[0013] Preferably, the substrate in step S1 comprises ITO (indium tin oxide) glass with a thickness of 10-15 nm.

[0014] Preferably, the photoresist in step S1 comprises PMMA photoresist with a solid content of 2-5 wt%.

[0015] Preferably, the thickness of the photoresist layer in step S1 is 100-500 nm.

[0016] Preferably, the coating in step S1 is performed by spin coating, with a spin coating speed of 1000-3000 rpm and a time of 30-90 s.

[0017] More preferably, the spin coating process further includes a heat treatment step, wherein the heat treatment temperature is 150-200℃ and the time is 10-20 min.

[0018] The purpose of the above heat treatment is mainly to remove excess solvent from the photoresist.

[0019] Preferably, in step S1, the photoresist layer is exposed by electron beam lithography, and the current used for electron beam lithography exposure is 30-50 nA, the voltage is 80-120 kV, and the corresponding pattern generator frequency is 20-40 MHz.

[0020] Preferably, the developing step S1 includes: immersing in a methyl isobutyl ketone / isopropanol mixed solvent for 30-90 seconds, followed by immersion in isopropanol for 5-40 seconds. More preferably, the volume ratio of methyl isobutyl ketone to isopropanol in the methyl isobutyl ketone / isopropanol mixed solvent is 1:(1-5).

[0021] Preferably, the thickness of the copper sacrificial layer in step S1 is 100-150 nm.

[0022] Preferably, the copper sacrificial layer deposited in step S1 is performed by thermal evaporation, and the thermal evaporation rate is 1-2 Å / s.

[0023] Preferably, step S1 involves immersing the photoresist in a resist remover solution, wherein the resist remover solution comprises N-methyl-2-pyrrolidone. More preferably, the immersion time in the resist remover solution is 4-8 hours.

[0024] In a specific embodiment of this application, the thickness of the PMMA adhesive refers to the distance from the surface of the copper sacrificial layer to the surface of the PMMA adhesive. In a specific embodiment of this application, the thickness of the PMMA adhesive is consistent with the height of the nanocylinders in the titanium dioxide metalens.

[0025] Preferably, in step S2, when developing the PMMA adhesive according to the pattern of the titanium dioxide metalens, a wavelength of [wavelength value missing] is used. The collimated light aligns the center of the titanium dioxide metalens pattern with the center of the copper sacrificial layer.

[0026] Preferably, the radial cross-sectional radius of the nanocylinder in step S2 is 30-150 nm.

[0027] More preferably, the radial cross-sectional radius of the nanocylinder described in step S2 satisfies the formula In the formula, x and y are the position coordinates (nm) in the plane of the superlens, λ is the wavelength of light in the medium (nm), f is the focal length of the designed superlens (nm), and φ is the target phase (rad) required by the superlens at that position.

[0028] Preferably, the coating in step S2 is performed by spin coating, with a spin coating speed of 1000-3000 rpm and a time of 30-90 s.

[0029] More preferably, the spin coating process further includes a heat treatment step, wherein the heat treatment temperature is 150-200℃ and the time is 20-30min.

[0030] Preferably, in step S2, the PMMA adhesive is exposed using electron beam lithography. The current used for electron beam lithography exposure is 3-5 nA, the voltage is 80-120 kV, and the corresponding pattern generator frequency is 2-4 MHz.

[0031] Preferably, the developing step S2 includes: immersing in a methyl isobutyl ketone / isopropanol mixed solvent for 30-90 seconds, followed by immersion in isopropanol for 5-40 seconds. More preferably, the volume ratio of methyl isobutyl ketone to isopropanol in the methyl isobutyl ketone / isopropanol mixed solvent is 1:(1-5).

[0032] Preferably, in step S2, titanium dioxide is deposited using atomic layer deposition (ALD), wherein the precursor used in the ALD process is tetrakis(dimethylamino)titanium, the oxidant is H2O, and the reaction gas is N2. More preferably, the flow rate of the reaction gas is 5-15 sccm.

[0033] Preferably, in step S3, titanium dioxide on the surface of PMMA adhesive is removed by reactive plasma etching.

[0034] Preferably, the reactive plasma etching method is carried out in an SF6 / Ar mixed atmosphere, wherein the flow rate of SF6 is 12-18 sccm and the flow rate of Ar is 10-30 sccm.

[0035] Preferably, in step S3, 500 nm ≤ ≤600 nm.

[0036] Preferably, the UV-curable adhesive in step S3 includes an acrylate-based curable adhesive.

[0037] More preferably, in step S3, the UV-curable adhesive is cured by irradiation with 350-450 nm UV light for 5-15 seconds.

[0038] Preferably, the FeCl3 solution in step S4 has a mass fraction of 42-48 wt%.

[0039] Preferably, the soaking time in step S4 is 36-48 h.

[0040] This invention also protects an integrated system of a titanium dioxide metalens and an optical fiber core, comprising, from top to bottom, an optical fiber holder, a metalens holder, a telephoto objective, a laser collimator, and a laser source. The optical fiber holder is fixedly connected to a first 5D displacement stage, the metalens holder is fixedly connected to a second 5D displacement stage, and the telephoto objective is fixedly connected to a 3D displacement stage. Each of the first, second, and 3D displacement stages has a through-hole for collimating light to pass through.

[0041] Compared with the prior art, the present invention has the following beneficial effects: The integrated alignment method for a titanium dioxide metalens and an optical fiber core provided by this invention involves first forming a copper sacrificial layer with a specific Fresnel band pattern on a substrate, then forming a titanium dioxide metalens on the surface of the sacrificial layer, and finally bonding the side of the metalens furthest from the substrate to the optical fiber end face using UV-curable adhesive. By using a sacrificial layer with a specific pattern as the basis for subsequent alignment, this invention can achieve precise positioning of the titanium dioxide metalens pattern and the optical fiber end face, improving alignment accuracy. Combined with a specific metalens structure, this invention can also improve the focusing efficiency of the metasurface on the optical fiber end face. Attached Figure Description

[0042] Figure 1 This is a schematic diagram of the processing flow of the integration method of titanium dioxide metalens and optical fiber core provided by the present invention.

[0043] Figure 2 This is a schematic diagram of the integrated alignment system of titanium dioxide metalens and optical fiber core provided by the present invention.

[0044] Figure 3 This is the GDS layout of the copper sacrificial layer provided in Embodiment 1 of the present invention.

[0045] Figure 4 This is a simulation result diagram of the transmission focusing function of the copper sacrificial layer provided in Embodiment 1 of the present invention.

[0046] Figure 5 This is a transmission phase scan diagram of a sub-unit in the titanium dioxide metalens pattern provided in Embodiment 1 of the present invention, where (a) is the transmittance of the sub-unit; and (b) is the phase change of the sub-unit.

[0047] Figure 6 The diagram shows (a) the electric field intensity at the focal plane and (b) the electric field intensity perpendicular to the focal plane of the titanium dioxide metalens provided in Embodiment 1 of the present invention.

[0048] Figure 7This is an optical microscopic image of the copper sacrificial layer aligned with the metalens provided in Embodiment 1 of the present invention.

[0049] Figure 8 This is a schematic diagram of the process of removing the ITO substrate and copper sacrificial layer in step S4 of Embodiment 1 of the present invention.

[0050] Figure 9 This is an optical micrograph of the fiber end face after the copper sacrificial layer has been removed in Embodiment 1 of the present invention.

[0051] Figure 10 The image shows a SEM image of the metalens in Embodiment 1 of the present invention, where (a) is an overall image of the metalens; (b) is an image showing the size changes of the cylinders arranged according to the target phase; and (c) is a detailed image of the metalens.

[0052] Figure 11 The image shown is a focal plane light field image obtained by actual measurement in Embodiment 1 of the present invention, wherein (a) is a light intensity map captured by CCD; and (b) is the extracted normalized grayscale light intensity map.

[0053] Figure 12 The image shows the focal light field of the integrated structure in Embodiment 1 of the present invention, where (a) is a normalized light intensity map perpendicular to the incident light field direction, and (b) is a normalized light intensity map along the incident light field direction.

[0054] Figure 13 (a) A focused schematic diagram of the titanium dioxide metasurface structure unit provided by the present invention; (b) A three-dimensional schematic diagram of the cylindrical subunit; (c) A side view of the cylinder; (d) A top view of the cylinder; (e) A schematic diagram of the change in the radius of the cylinder during the propagation phase.

[0055] Figure 14 This is a phase change curve of the titanium dioxide metalens subunit provided in Embodiment 1 of the present invention.

[0056] Figure 15 The figures are phase change curves of the subunits in the titanium dioxide metalenses provided in Examples 2-4 of the present invention, where (a) is Example 2, (b) is Example 3, and (c) is Example 4.

[0057] Figure 16 The figures are phase change curves of the subunits in the titanium dioxide metalens provided in Comparative Examples 1-2 of the present invention, where (a) is Comparative Example 1 and (b) is Comparative Example 2.

[0058] Figure 17 The figures are phase change curves of the subunits in the titanium dioxide metalens provided in Examples 5-7 of the present invention, where (a) is Example 5, (b) is Example 6, and (c) is Example 7.

[0059] Figure 18 The figures are phase change curves of the subunits in the titanium dioxide metalens provided in Comparative Examples 3-4 of the present invention, where (a) is Comparative Example 3 and (b) is Comparative Example 4.

[0060] Figure 19 The images show the copper sacrificial layer GDS layouts provided in Embodiments 1, 8, 9 and Comparative Example 5 of the present invention, where (a) is Embodiment 1, (b) is Embodiment 8, (c) is Embodiment 9 and (d) is Comparative Example 5. Detailed Implementation

[0061] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents. Information on the raw materials used in some embodiments and comparative examples is as follows: PMMA Glue-1: PMMA A4 glue, purchased from MICRO CHEM, grade 950 PMMA A4, with a solid content of 4% (the molecular weight of PMMA polymer is 950 kg / mol).

[0062] PMMA Glue-2: PMMA A7 glue, purchased from MICRO CHEM, grade 950 PMMA A7, with a solid content of 7% (the molecular weight of PMMA polymer is 950 kg / mol).

[0063] UV-curing adhesive: Acrylic ester adhesive, Kraft K-3181, purchased from Guangdong Kraft New Material Technology Co., Ltd.

[0064] Adhesive remover: Remover PG stripper, the main component of which is N-methyl-2-pyrrolidone, purchased from MICRO CHEM.

[0065] Example 1 An integrated alignment method for a titanium dioxide metalens and an optical fiber core includes the following steps: S1. PMMA resist-1 is uniformly coated onto a clean ITO glass substrate at 2000 rpm for 60 s, resulting in a resist thickness of 300 nm. The substrate is then heated at 180°C for 15 min. Subsequently, the required sacrificial layer pattern is exposed using electron beam lithography (EBL, e-line plus) at an exposure condition of 40 nA and 100 kV. Afterward, the substrate is developed with a mixed solvent of MIBK:IPA = 1:3 for 60 s, fixed with IPA solution for 20 s, and then copper is deposited as the sacrificial layer using a thermal evaporation machine at a deposition rate of 1.5 Å / s, resulting in a film thickness of 120 nm. The substrate is then immersed in a resist stripping solution for 4 h to remove excess photoresist. The pattern of the copper sacrificial layer is a Fresnel zone ring, which includes multiple concentric rings. The inner and outer radii of the concentric rings satisfy the following conditions: ,in Let n be the radius of the concentric annulus, where n is a positive integer; when n is odd, ... This represents the outer diameter value; when n is an even number, This refers to the inner diameter value; S2. PMMA adhesive-2 was uniformly coated onto the copper sacrificial layer at a spin speed of 2000 rpm for 60 s, resulting in an adhesive thickness of 850 nm. The coating was then heated on a 180℃ heating stage for 30 min. The pattern of the titanium dioxide metalens was exposed onto the PMMA adhesive-2 above the copper sacrificial layer using electron beam lithography at an exposure condition of 4 nA and 100 kV. Development was performed using a mixed solvent of MIBK:IPA = 1:3 for 60 s, followed by fixing with IPA solution for 20 s, resulting in PMMA adhesive-2 with grooves. Titanium dioxide was deposited in the grooves using atomic layer deposition (ALD) with tetrakis(dimethylamino)titanium as the precursor and H2O as the oxidant. The mixture was purged with nitrogen at a flow rate of 10 sccm to obtain the titanium dioxide metalens. The titanium dioxide metalens comprises several nanocylinders, wherein the distance between the centers of any two adjacent nanocylinders is 320 nm, and the radial cross-sectional radius of the nanocylinders is 40-140 nm. nm; the radial cross-sectional radius of the nanocylinder satisfies the formula In the formula, x and y are the position coordinates (nm) within the plane of the superlens, λ is the wavelength of light in the medium (nm), f is the focal length of the designed superlens (nm), and φ is the target phase (rad) required by the superlens at that position. The radius of the cylinder at a specific position can be selected according to the required phase based on the table below, such as... Figure 10 As shown: S3. Use a reactive plasma etching machine to etch TiO2 onto the surface of PMMA adhesive-2, with an SF6 flux of 15 sccm and an Ar flux of 20 sccm. Then, using an integrated system of a titanium dioxide metalens and an optical fiber core, collimated light with a wavelength of 532 nm is used to align the center of the titanium dioxide metalens obtained in step S2 with the center of the end face of the optical fiber core. After alignment, apply UV-curable adhesive to the end face of the optical fiber, and cure it by UV irradiation for 10 s after close proximity to form an integrated structure. S4. Immerse the integrated structure obtained in step S3 in a 45 wt% FeCl3 solution for 36 h to remove the ITO substrate and copper sacrificial layer, thereby fabricating a titanium dioxide metalens on the end face of the optical fiber core.

[0066] The integrated system of titanium dioxide metalens and optical fiber core used in this embodiment is specifically as follows: Figure 2 As shown, from top to bottom, the system includes a fiber optic holder, a metasurface holder, a telephoto lens, a laser collimator, and a laser source. The fiber optic holder is fixedly connected to a first 5D displacement stage, the metasurface holder is fixedly connected to a second 5D displacement stage, and the telephoto lens is fixedly connected to a 3D displacement stage. Each of the first, second, and 3D displacement stages has a through-hole for the laser to pass through.

[0067] Examples 2-4 and Comparative Examples 1-2 The only difference between Examples 2-4, Comparative Examples 1-2, and Example 1 is the thickness of the PMMA adhesive-2 coating in step S2 (i.e., the height of the nanocylinders in the titanium dioxide metalens is different), as shown in Table 1 below: Table 1. Examples 5-7 and Comparative Examples 3-4 The only difference between Examples 5-7, Comparative Examples 3-4, and Example 1 is the distance between the centers of the nanocylinders in the titanium dioxide metalens in step S2, as shown in Table 2 below: Table 2. Examples 8-9 and Comparative Example 5 The only difference between Examples 8-9 and Comparative Example 5 and Example 1 is that: In step S1 of Example 8, the pattern of the copper sacrificial layer is based on the zone plate of Example 1, except that the adjacent intermediate rings are removed, and it only includes a central circle with a diameter of 30 μm and a ring concentric with the odd-order central circle; Example 9 is based on the zone plate of Example 1, except that the adjacent intermediate rings are removed; Comparative Example 5 is a circle without the zone plate rings, such as... Figure 19 As shown.

[0068] Table 3. Performance testing Focusing efficiency test: The light intensity of the sample surface light field images of the integrated structures obtained in Examples 1-7 and Comparative Examples 1-4, and the copper sacrificial layer in Examples 8-9 and Comparative Example 5 is integrated to obtain the total light field energy. The position of half width at half maximum (WHM) is found. The light intensity of the focal plane is integrated within a range of three times the WHM, and then divided by the light intensity integral within the sample surface to obtain the focusing efficiency of the lens or zone plate.

[0069] Simulation of transmission focusing function: Simulation analysis and calculation were performed using Lumercial FDTD, COMSOL Multiphysic, and MATLAB.

[0070] Metasurface sub-unit scanning: obtained by COMSOL simulation.

[0071] Focal plane light field image and electric field intensity test: obtained by CCD.

[0072] The results of the above performance tests are shown in Tables 4 and 5 below. Figure 14-19 As shown: Table 4 Table 5 according to Figure 4 It can be seen that the zone plate does indeed have a transmission focusing function.

[0073] according to Figure 5 It can be confirmed that the optical field at the fiber end face provided in this application can achieve full coverage of the 2π phase, with high transmittance and a minimum linewidth of around 50 nm.

[0074] according to Figure 10 This application can prepare titanium dioxide metalenses with good morphology, and the largest and smallest nanocylindrical structures can maintain their morphology during preparation and transfer.

[0075] Figure 11 To obtain the light intensity map and normalized grayscale image captured by CCD, based on Figure 11 It is clear that the lens provided in Embodiment 1 of this application has a focusing efficiency of 55%. Calculations show that its numerical aperture NA = 0.2723 and depth of focus DOF ​​= 14.3498 μm.

[0076] Figure 12 Let be the light intensity along the X direction on the focal plane of the lens, given by Figure 12As can be seen, the half-width at half-maximum (FWHM) of the lens spot in Embodiment 1 of this application is about 1 μm, which is smaller than the minimum spot size of the ideal Airy disk, thus achieving focusing under diffraction limit. Figure 12 b represents the central light field data obtained by moving the displacement stage along the light path near the focal point, with each movement being 3.3 μm. By statistically analyzing the light intensity at the center position and plotting the normalized light intensity map, observations show that the focal depth is approximately 14 μm, consistent with the theoretically calculated focal depth.

[0077] Figure 14 This is a phase change curve of the subunit in the titanium dioxide metalens provided in Embodiment 1 of the present invention. According to... Figure 14 It is evident that the titanium dioxide metalens provided in Embodiment 1 of this application can achieve full coverage of the 2π phase.

[0078] Figure 15 The figures are phase change curves of the subunits in the titanium dioxide metalens provided in Examples 2-4 of the present invention, where (a) is Example 2, (b) is Example 3, and (c) is Example 4. Figure 16 The figures shown are phase change curves of the sub-units in the titanium dioxide metalenses provided in Comparative Examples 1-2 of this invention, where (a) is Comparative Example 1 and (b) is Comparative Example 2. According to... Figure 15-16 As can be seen, the titanium dioxide metalens provided in this application embodiment can achieve full coverage of the 2π phase, except for the region of severe phase change caused by resonance (which strongly restricts the propagation of light and results in low transmittance), but the titanium dioxide metalens provided in the comparative example cannot achieve this.

[0079] Figure 17 The figures are phase change curves of the subunits in the titanium dioxide metalens provided in Examples 6-8 of the present invention, where (a) is Example 5, (b) is Example 6, and (c) is Example 7. Figure 18 These are phase change curves of the subunits in the titanium dioxide metalenses provided in Comparative Examples 3-4 of the present invention, where (a) is Comparative Example 3 and (b) is Comparative Example 4. According to... Figure 17-18 It is evident that the phase coverage can be adjusted by changing the period of the nanopillar units. It is important to note that the diameter of the nanopillars should be smaller than the period, and to improve the fabrication process window, the minimum linewidth should be greater than 50 nm. That is, the minimum diameter of the nanopillars should be greater than 50 nm, and the maximum diameter should be less than the period length minus 50 nm. The phase coverage of the nanopillar units, designed with periods of 280 nm, 300 nm, and 340 nm, is as follows: Figure 17As shown, the phase coverage increases with increasing period, with the 300nm to 340nm period showing the best phase coverage. Changing the period of the nanopillar to 250nm and 400nm results in the following phase abrupt changes: Figure 18 As shown, it can be seen that when the period of the nanopillar is 250 nm, it is impossible to cover the 2π phase range. When the period of the nanopillar is 400 nm, it can also cover the 2π phase, but since its period is larger than the equivalent wavelength of the incident light, it will produce severe high-order diffraction, generating high-order diffraction orders like a grating, which will reduce its efficiency.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. An integrated alignment method for a titanium dioxide metalens and an optical fiber core, characterized in that, Includes the following steps: S1. A photoresist layer is coated on the substrate surface. Exposure and development are performed according to the pattern of the copper sacrificial layer. After forming grooves in the copper sacrificial layer pattern on the photoresist layer surface, the copper sacrificial layer is deposited, and then excess photoresist is removed. The pattern of the copper sacrificial layer is a Fresnel zone ring, which includes multiple concentric rings. The inner and outer radii of the concentric rings satisfy... ,in Let n be the radius of the concentric annulus, where n is a positive integer; when n is odd, ... This represents the outer diameter value; when n is an even number, This refers to the inner diameter value; S2. A PMMA adhesive with a thickness of 700-1000 nm is coated on the surface of the copper sacrificial layer obtained in step S1. The PMMA adhesive is then exposed and developed according to the pattern of the titanium dioxide metalens. The titanium dioxide metalens comprises several nanocylinders, wherein the distance between the centers of any two adjacent nanocylinders is 280-350 nm. After development, a grooved PMMA adhesive is obtained. Titanium dioxide is deposited in the grooves to obtain the titanium dioxide metalens. The solid content of the PMMA adhesive is 7-10 wt%. S3. Remove the titanium dioxide from the surface of the PMMA adhesive, then pass it through a wavelength of [wavelength value missing]. The collimated light aligns the center of the titanium dioxide metalens obtained in step S2 with the center of the fiber core end face. The fiber core end face and the titanium dioxide metalens are then bonded together using UV-curable adhesive to form an integrated structure. S4. Immerse the integrated structure obtained in step S3 in FeCl3 solution to remove the substrate and copper sacrificial layer, and a titanium dioxide metalens can be prepared on the end face of the optical fiber core.

2. The integrated alignment method of titanium dioxide metalens and optical fiber core as described in claim 1, characterized in that, The photoresist in step S1 includes PMMA photoresist with a solid content of 2-5 wt%.

3. The integrated alignment method of titanium dioxide metalens and optical fiber core as described in claim 1 or 2, characterized in that, The thickness of the photoresist layer in step S1 is 100-500 nm.

4. The integrated alignment method of titanium dioxide metalens and optical fiber core as described in claim 1, characterized in that, The radial cross-sectional radius of the nanocylinder described in step S2 is 30-150 nm.

5. The integrated alignment method of titanium dioxide metalens and optical fiber core as described in claim 1, characterized in that, In step S3, titanium dioxide is removed from the surface of PMMA adhesive by reactive plasma etching.

6. The integrated alignment method of titanium dioxide metalens and optical fiber core as described in claim 5, characterized in that, The reactive plasma etching method is carried out in an SF6 / Ar mixed atmosphere, wherein the flow rate of SF6 is 12-18 sccm and the flow rate of Ar is 10-30 sccm.

7. The integrated alignment method of titanium dioxide metalens and optical fiber core as described in claim 1, characterized in that, In step S3, 500 nm ≤ ≤600 nm.

8. The integrated alignment method of titanium dioxide metalens and optical fiber core as described in claim 1, characterized in that, The UV-curable adhesive mentioned in step S3 includes acrylate-based curable adhesives.

9. The integrated alignment method of titanium dioxide metalens and optical fiber core as described in claim 1, characterized in that, Includes at least one of the following (1)-(2): (1) The mass fraction of the FeCl3 solution in step S4 is 42-48 wt% (2) The soaking time in step S4 is 36-48 h.

10. An integrated alignment system for a titanium dioxide metalens and an optical fiber core, characterized in that, The components, arranged from top to bottom, include an optical fiber holder, a metasurface holder, a telephoto lens, a laser collimator, and a laser source. The optical fiber holder is fixedly connected to a first 5D displacement stage, the metasurface holder is fixedly connected to a second 5D displacement stage, and the telephoto lens is fixedly connected to a 3D displacement stage. Each of the first, second, and 3D displacement stages has a through-hole for collimating light to pass through.